Splenic artery pseudoaneurysm as a complication of pancreatic pseudocyst - Micković Saša; Mitrović Miroslav; Stanković Nebojša; Bezmarević Mihailo; Jovanović Milan; Mirković Darko; Tufegdžić Ivana; Nikolić-Micković Irena (Vojnosanitetski Pregled)
Introduction. Pancreatic pseudocyst presented as pseudoaneurysm of the splenic artery is a potential serious complication in patients with chronic pancreatitis. Case report. A 42-year-old male patient with a long-standing evolution of chronic pancreatitis and 8-year long evolution of pancreas pseudocyst was referred to the Military Medical Academy, Belgrade due to worsening of the general condition. At admission, the patient was cachectic, febrile, and had the increased values of amylases in urine and sedimentation (SE). After clinical and diagnostic examination: laboratory assessment, esophagogastroduodenoscopy (EGDS), ultrasonography (US), endoscopic ultrasonography (EUS), multislice computed scanner (MSCT) angiography, pseudoaneurysm was found caused by the conversion of pseudocyst on the basis of chronic pancreatitis. The patient was operated on after founding pancreatic pseudocyst, which caused erosion of the splenic artery and their mutual communication. Postoperative course was duly preceded without complications with one year follow-up. Conclusion. Angiography is the most reliable and the safest method for diagnosing hemorrhagic pseudocysts when they clinically present as pseudoaneurysms. A potentially dangerous complication in the presented case was treated surgically with excellent postoperative results.